Satisfaction and Preferences for Infusion Therapies in Advanced Parkinson’s Disease—Patient Perspective - Julia Węgrzynek-Gallina; Tomasz Chmiela; Michał Borończyk; Aleksandra Buczek; Patrycja Hudzińska; Hubert Bigajski; Damian Waksmundzki; Justyna Gawryluk; Joanna Siuda (Medicina)
Background and Objectives: The rapid growth of the number of advanced Parkinson’s disease (PD) patients has caused a significant increase in the use of device-aided therapies (DATs), including levodopa–carbidopa intestinal gel (LCIG) and continuous subcutaneous apomorphine infusion (CSAI). The objective of this study was to evaluate patients’ satisfaction and the factors influencing preferences for CSAI and LCIG. Materials and Methods: The research focused on individuals diagnosed with advanced PD undergoing DAT at the Neurology Department of the University Hospital in Katowice. A telephone survey conducted between June and July 2024 evaluated the experiences of patients with LCIG and CSAI. The Parkinson’s Disease Questionnaire (PDQ-8) and the Stress Scale for Family Caregivers (BSFC-s) were applied. Based on medical record data comprising reasons for the exclusion of individuals, disease-related and treatment data were collected. Results: Among the original cohort of 64 patients, 50 completed the survey, including 31 who might choose between infusion therapies. The average patient ages were 70.6 ± 4.7 (CSAI) and 71.2 ± 7.2 years (LCIG), with disease durations of 15 (IQR: 12–19) and 18 (IQR: 13–19) years, respectively. LCIG patients presented higher PDQ-8 scores (20 (IQR: 13–27) vs. 13 (IQR: 6–19), p = 0.008), and higher BSFC-s scores (19 (IQR: 12–21) vs. 9 (IQR: 2.5–13), p = 0.011). Furthermore, significant factors influencing patient preferences included fear of surgery (75% vs. 36.8%, p = 0.043) and concerns about DAT safety (83.3% vs. 47.4%, p = 0.049). Conclusions: LCIG and CSAI therapies offer benefits and disadvantages, with safety concerns and fear of surgery seeming to be decisive in the decision-making process.